Penerapan Algoritma Zhutakaoka Pada Aplikasi Pengenalan Rambu K3 - Evi Ramadani (Journal of Informatics Management and Information Technology, 2021)
Abstract?K3 signs are very important signs in work to avoid work accidents and there are many kinds of K3 signs such as pictures and symbols so that these K3 signs are very useful for workers both in buildings and in projects. So that workers avoid work accidents both in the work environment or outside the work environment. For that we need an application that contains the search for K3 signs. Where workers can learn these signs. This K3 sign application is used by workers by searching from an existing application in the application that has been made. And it can be understood if the worker succeeds in looking for the K3 signs that have been determined according to the existing pattern, still searching for solutions in the application. Search for K3 signs is designed using the String matching method, application development uses the UML design method and is built on the Android platform.